2020
DOI: 10.3389/fnins.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatic Airway Vagal Hypertonia Involves Chloride Dyshomeostasis of Preganglionic Neurons in Rats

Abstract: Airway vagal hypertonia is closely related to the severity of asthma; however, the mechanisms of its genesis are unclear. This study aims to prove that asthmatic airway vagal hypertonia involves neuronal Cl − dyshomeostasis. The experimental airway allergy model was prepared with ovalbumin in male adult Sprague-Dawley rats. Plethysmography was used to evaluate airway vagal response to intracisternally injected γ-aminobutyric acid (GABA). Immunofluorescent staining and Western-blot assay were used to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Meanwhile, Western-blot essay showed increased expression of ECP1 in the lungs, indicating infiltration of eosinophils and pulmonary inflammation. These functional and inflammatory changes suggest a successful model of allergic asthma, as we have previously reported (22).…”
Section: Discussionsupporting
confidence: 75%
“…Meanwhile, Western-blot essay showed increased expression of ECP1 in the lungs, indicating infiltration of eosinophils and pulmonary inflammation. These functional and inflammatory changes suggest a successful model of allergic asthma, as we have previously reported (22).…”
Section: Discussionsupporting
confidence: 75%
“…He and colleagues examined the role of neuronal Cl − homeostasis in asthma [ 163 ]. It is known that vagal hypertonia is closely related to the severity of asthma as it controls airway smooth muscle.…”
Section: Other Disease Statesmentioning
confidence: 99%
“…The mechanism behind this hypertonia, however, was unclear. They found increased microglial activation in the brainstem, particularly in the nucleus accumbens [ 163 ]. He et al then identified an upregulation of NKCC1 and downregulation of KCC2 in the nucleus accumbens, which would augment the excitatory vagal response.…”
Section: Other Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that minocycline can inhibit the proliferation of T lymphocytes stimulated by GITRL and regulate the expression of IL-17 and RORγt in T lymphocytes [ 44 ]. Moreover, other studies have found that minocycline can reduce the symptoms of asthma [ 45 , 46 ]. As blocking GITRL showed a protective effect for asthma in our research and other research on GITRL-associated clinical trials and blocking or agonist drugs of GITR are relatively mature, GITRL may be a therapeutic target for asthma in the future, which has important clinical significance.…”
Section: Discussionmentioning
confidence: 99%